Agenda setting about the war in Ukraine - Fetoshi, Arben (Teorija in praksa, 2023)
The article examines agenda-setting factors in Kosovo concerning the war in Ukraine. Due to the complex situation in the Western Balkans and the context of the tensions between Kosovo and Serbia, the presented research explains the role played by television in the hybrid media environment as the most important source of information in the crisis. The research looks at how television has impacted how the public views the war in Ukraine, and how it has covered the situation both before and after the invasion. A mixed methodology consisting of a questionnaire, television monitoring, content analysis, and desk research was thus adopted on the empirical level. On this level, 716 news stories were analysed between 1 February and 31 March 2022 and a survey with 1,312 respondents from Kosovo was conducted in April and May 2022 to identify different agents in the agenda setting and how that works with respect to the war in Ukraine. The research results show that the war in Ukraine has dominated the agenda of television stations in Kosovo, while the effects of their reporting vary according to the audience’s demographic characteristics
Keywords: agenda setting; empirična analiza; framing; Javno mnenje; medijska agenda; news selection; oblikovanje medijske agende; raziskava; rusko-ukrajinska vojna; Russian-Ukrain war; selekcija poročanja; television news; Tuje javno mnenje; vojna; vojna v Ukrajini; war